2020
DOI: 10.1155/2020/8886612
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Advanced Glycation End-Products (AGEs) on Proliferation and Apoptosis of Primary Stem Cells: A Systematic Review

Abstract: Stem cell-based regenerative therapies hold great promises to treat a wide spectrum of diseases. However, stem cell engraftment and survival are still challenging due to an unfavorable transplantation environment. Advanced glycation end-products (AGEs) can contribute to the generation of these harmful conditions. AGEs are a heterogeneous group of glycated products, nonenzymatically formed when proteins and/or lipids become glycated and oxidized. Our typical Western diet as well as cigarettes contain high AGEs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 90 publications
(151 reference statements)
1
11
0
Order By: Relevance
“…Even if they provide new insights into tissue regeneration, stem cells are transplanted in the border zone of MI with increased oxidative stress, inflammation, and AGEs' levels. Previous studies have shown that increased levels of AGEs affect stem cells' properties, i.e., by reducing their proliferation and migration properties [28]. Recently, we have demonstrated that the same adverse effects of AGEs apply to CASCs' properties in vitro [29].…”
Section: Combining Cascs and Pm To Enhance Cardiac Repairmentioning
confidence: 80%
See 1 more Smart Citation
“…Even if they provide new insights into tissue regeneration, stem cells are transplanted in the border zone of MI with increased oxidative stress, inflammation, and AGEs' levels. Previous studies have shown that increased levels of AGEs affect stem cells' properties, i.e., by reducing their proliferation and migration properties [28]. Recently, we have demonstrated that the same adverse effects of AGEs apply to CASCs' properties in vitro [29].…”
Section: Combining Cascs and Pm To Enhance Cardiac Repairmentioning
confidence: 80%
“…These contribute to increased AGEs levels in patients suffering from MI. Recently, systematic review analysis [28] revealed that AGEs affect the viability and proliferation capacity of multiple types of stem cells in vitro, including CASCs [29], thereby affecting their therapeutic potential. These effects occur throughout several underlying mechanisms including excessive reactive oxygen species (ROS) generation, activation of the receptor for AGEs (RAGE), or via apoptotic pathways.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that SARS-CoV-2 activates mRAGE at pulmonary alveolar cells, leading to severe inflammatory reactions (Yalcin Kehribar et al, 2020). It has been confirmed that the concentration of sRAGE is reduced with aging, which might explain the susceptibility of old age to COVID-19 (Evens et al, 2020). However, in young and asymptomatic COVID-19 patients, the concentration of sRAGE is high.…”
Section: Testosterone and Acute Lung Injurymentioning
confidence: 97%
“…But the stem cells also bring us a question: how to maximize their regenerative efficiency after transplantation? The fate of stem cells can be more dynamic than we expected including adhesion [ 4 ], migration [ 5 ], proliferation, and apoptosis [ 6 ]. Besides, the survival rate of stem cells after transplantation also remained unsatisfactory.…”
Section: Introductionmentioning
confidence: 99%